Utilization of Canva Infographics to Improve Learning Outcomes of Procedure Texts - Mariani, Titin; Lubis, M. Joharis; Hutagalung, Surya Masniari (PT. Riset Press International, 2025)
This article describes improving students' procedure text learning outcomes using Canva infographics. The research method used is descriptive quantitative. This research uses instruments like pre-test and post-test with 20 questions. The numerical data will be discussed in detail by describing the research variables. The research subjects were 25 seventh-grade junior high school students. This study obtained the following results: there was an increase in student learning outcomes in learning procedure text before and after using Canva infographics. Students completed the pretest with an overall average score of 66.5, increasing to 75.1 for the posttest average score. There was an increase in pre-test classical completeness from 44% to 80% compared to the post-test classical completeness score.